1965
DOI: 10.1007/bf02635573
|View full text |Cite
|
Sign up to set email alerts
|

Lipid analysis by quantitative thin‐layer chromatography

Abstract: Techniques for the quantitative analysis of lipids using thin‐layer chromatography (TLC) are reviewed. The general procedures are divided into two groups on the basis of whether or not the methods involve the recovery of substances from chromatoplates. Recovery methods are elaborated under detection of spots, recovery of substances and quantification. Methods are described for the recovery of labile compounds from chromatoplates and for the determination of the structures of triglycerides and lecithins. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

1967
1967
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(24 citation statements)
references
References 85 publications
0
24
0
Order By: Relevance
“…Completeness of the lipid extraction procedure was checked by measuring the quantity of fatty acids released after the extracted residue from one whole brain and from one batch of membranes saponified with 10% K O H in 75% aqueous ethanol. After acidification, the fatty acids were extracted and then quantitated by two independent procedures for lipid mass after resolution by thin-layer chromatography: photodensitometry (Privett et a/., 1965) and scintillation quenching (Snyder and Moehl, 1969). Both methods showed less than 0.5% fatty acids present in both tissue residues and indicated that the Bligh and Dyer extraction procedure was quantitative for removing lipids from rat brain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Completeness of the lipid extraction procedure was checked by measuring the quantity of fatty acids released after the extracted residue from one whole brain and from one batch of membranes saponified with 10% K O H in 75% aqueous ethanol. After acidification, the fatty acids were extracted and then quantitated by two independent procedures for lipid mass after resolution by thin-layer chromatography: photodensitometry (Privett et a/., 1965) and scintillation quenching (Snyder and Moehl, 1969). Both methods showed less than 0.5% fatty acids present in both tissue residues and indicated that the Bligh and Dyer extraction procedure was quantitative for removing lipids from rat brain.…”
Section: Methodsmentioning
confidence: 99%
“…short of the first solvent front. This technique resolved cholesterol ( R F 0.9), ceramides (RF 0.8), and cerebrosides (RF 0.5) which were quantitated by photodensitometry (Privett et a/., 1965).…”
Section: Methodsmentioning
confidence: 99%
“…This differs from the practice of determining the lipid content gravimetrically (Privett et al, 1965), which can overestimate the amount of saponifiable lipid in the biomass. Total lipids were extracted from dried microbial cells based on the protocol developed by Bligh and Dyer (Bligh and Dyer, 1959).…”
Section: Total Lipid Analysismentioning
confidence: 98%
“…coli had increased to concentrations significantly higher than levels in rabbits 3 hr after injection ( p < .01). '1 and 4), 3 hr after challenge (2 and 5), and 24 hr after challenge (3 and 6 ) ; free cholesterol (7) ; phosphatidyl choline (8) ; triolein (9) ; cholesterol stesrate (10) ; oleic acid (11) ; and mixture of 7-11 (12). …”
mentioning
confidence: 99%